XCP for shared-access multi-rate media. - Abrantes, Filipe (Computer communication review.)
The eXplicit Control Protocol (XCP) was developed to overcome some of the limitations of TCP, such as low utilization in high bandwidth delay product networks, unstable throughput, large queue build-up, and limited fairness. XCP, however, requires that each queue controller in a path knows the exact capacity of its link. In shared access media, e.g. IEEE 802.11, knowing the actual capacity of the channel is a difficult task.In this paper we propose modifications to the XCP algorithm that enable the utilization of XCP even when the capacity of a link is unknown. These modifications are validated through simulation.We also present the results of a comparison between the performance of the modified XCP and TCP, where XCP controlled flows result more stable, fairness increases, and the network delay becomes lower. In addition, as the bandwidth delay product increases, XCP is able to maintain near-maximum utilization while TCP decreases utilization.